DETERMINAN KINERJA KEUANGAN PEMERINTAH KOTA LANGSA - Mutaqin, Muhammad Darul; Tuti Meutia; Agustina Nurul Fajriah (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This research aims to determine the influence of intergovernmental revenue, wealth, government size on financial performance. This research data is secondary data. The sampling technique uses a saturated sampling method. The data collection method used in this research is Quantitative Data. The quantitative data in this research is in the form of budget realization reports and balance sheets from the Langsa City LKPD for 2013-2022. The data analysis method used in this research is multiple linear regression analysis using SPSS (Statistical Package for the Social Science) software. The results of this research show that the intergovernmental revenue, wealth, and government size variables have a significant influence on the financial performance of the Langsa city regional government, simultaneously intergovernmental revenue, wealth, government size have a significant influence on the Langsa city regional government. The limitations of this research were that it was conducted over a too small period of 10 years, namely 2013-2022, resulting in limited and missing data in certain periods or incomplete sources, which could affect the analysis and generalization of the findings. There are suggestions to look more deeply into the influence of intergovernmental revenue, wealth, and government size on regional government financial performance by considering additional variables. Variables such as capital expenditures, BPK audit findings, audit opinions, leverage, and legislative measures can be included to expand understanding of the factors that influence financial performance. In addition, it is recommended to develop this research by considering wealth as a moderating variable, which can moderate the influence of other variables on financial performance.